Dispersion of bamboo type multi-wall carbon nanotubes in calf-thymus double stranded DNA - Primo, Emiliano Nicolás (2013)
We report for the first time the use of double stranded calf-thymus DNA (dsDNA) to successfully disperse bamboo-like multi-walled carbon nanotubes (bCNT). The dispersion and the modified electrodes were studied by different spectroscopic, microscopic and electrochemical techniques. The drastic treatment for dispersing the bCNT (45 min sonication in a 50% (v/v) ethanol:water solution), produces a partial denaturation and a decrease in the length of dsDNA that facilitates the dispersion of CNT and makes possible an efficient electron transfer of guanine residues to the electrode. A critical analysis of the influence of different experimental conditions on the efficiency of the dispersion and on the performance of glassy carbon electrodes (GCE) modified with bCNT–dsDNA dispersion is also reported. The electron transfer of redox probes and guanine residues was more efficient at GCE modified with bCNT dispersed in dsDNA than at GCE modified with hollow CNT (hCNT) dispersed in dsDNA, demonstrating the importance of the presence of bCNT.